Size-controlled polymer-coated nanoparticles as efficient compatibilizers for polymer blends - Kwon, Taegyun; Kim, Taesu; Ali, Fathilah; Kang, Dong Jin; Yoo, Misang; Bang, Joona; Lee, Wonbo; Kim, Bumjoon J. (American Chemical Society, 2011)
Polymer-coated gold nanoparticles (Au NPs) with controlled size and surface chemistry were successfully synthesized and applied to tailor the structures and properties of polytriphenylamine (PTPA) and polystyrene (PS) blends. Two different polymer-coated Au NPs with sizes of 5.9 nm (Au NP-1) and 20.7 nm (Au NP-2) were designed to be thermally stable above 200 C and neutral to both PS and PTPA phases. Hence, both Au NPs localize at the PS/PTPA interface and function as compatibilizers in the PS/PTPA blend. To show the compatibilizing effect of the particles, the morphological behaviors of PS/PTPA blends containing different particle volume fractions (ϕp) of Au NPs were observed using cross-sectional TEM, and for quantitative analysis, the size distribution of PTPA droplets in the PS matrix was obtained for each sample. The number-average droplet diameter (Dn) of the PTPA domain in the blend was dramatically reduced from 1.4 μmto 500 nm at a small ϕp of 1.0 vol % Au NP-1. The same trend of decreasing Dn was also observed with the addition of larger Au NP-2, but a higher ϕp was required to obtain the same amount of reduction in the PTPA droplet size. The ϕp required to fully cover the PS/PTPA interface as a packed monolayer of Au NPs was calculated as 0.98 vol % for Au NP-1 and 3.38 vol % for Au NP-2, thus giving excellent agreement with critical ϕp values for the saturation of the PTPA droplet diameter Dn. To demonstrate the effectiveness of Au NPs as compatibilizers, polystyrene-b-poly(triphenylamine) (PS-b-PTPA) block copolymers were also synthesized and used as compatibilizers in the PS/PTPA blend. The decrease in Dn with the addition of PS-b-PTPA was always smaller than that with addition of Au NP-1 at the same ϕp, indicating that Au NPs are more effective compatibilizers. This different behavior can be attributed to the presence of PS-b-PTPA compatibilizers as micelles or free chains in the homopolymer matrix. In contrast, most Au NPs were strongly adsorbed to the PS/PTPA interface.